Leapfrogging into Digital Credit: The Trade-off between Financial Inclusion and Portfolio Risk in Sub-Saharan Africa: A Comparative Analysis of Kenya and Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
The rapid proliferation of mobile-based lending across Sub-Saharan Africa has generated a fundamental tension: digital credit promises financial inclusion at scale yet carries inherent portfolio risks that threaten lender stability and borrower welfare. This study examines this inclusion-risk trade-off through a comparative analysis of Kenya, a mature digital credit market, and Ethiopia, an emerging latecomer with significant leapfrogging potential. Drawing on bank-level loan performance data, regulatory frameworks, and institutional analysis spanning 2014–2025, the study documents Kenya's